Jessie Kleemann’s Art of Survival - W. Norman, David (Peripeti, 2022)
In her work as an educator, actor, poet and visual artist, Jessie Kleemann has persistently expanded the limits of arts discourse in Kalaallit Nunaat, not least through her unique approach to body art informed by historical Kalaallit theatrical forms and antimimetic dramaturgy. Emphasizing how Kleemann’s embodied practice prompts reflection on the potential for action amid environmental collapse, this essay situates her work alongside schools of thought that have theorized the body during moments of crisis. I focus on Kleemann’s early experimentation with analog video and recent ecocritical poetry, aligning her work with traditions ranging from ancestral Inuit performance genres to post-1945 action art and contemporary practices advocating on behalf of missing and murdered Indigenous women and girls. Kleemann’s methods, refracted through these traditions, place embodied action at the center of efforts to form more ethical relations.